Pemutusan Kontrak Secara Sepihak oleh Pejabat Pembuat Komitmen (PPK) Terhadap Penyedia Barang/Jasa - Gusti Ngurah Anom Widyarta; I Wayan Arthanaya; Luh Putu Suryani (Fakultas Hukum Universitas Warmadewa, 2019)
As a legal state, every administration of government affairs must be based on applicable law. As a State that embraces decentralization it means that government affairs consist of central government affairs and regional government affairs. This means that there is a set of central government tools and local government instruments, which are given autonomy, namely freedom and independence to regulate and manage regional household affairs. In carrying out the functions of government, it is definitely needed by providers of goods / services that support the optimal performance of the agency. The contract for the procurement of goods / services between PPK and the goods / services provider contains the obligations and rights of the parties in the context of carrying out the procurement of goods / services. In the implementation of contracts, often the goods / services provider does not carry out its obligations perfectly in accordance with what has been stated in the contract. This can result in the unilateral termination of the contract by the PPK, and in this study discussed the procedure for terminating contracts in the procurement of goods / services as well as the legal consequences of unilateral termination of contracts by Commitment Makers (PPK) to providers of goods. This study is a type of Normative Legal Research, using a statutory approach, while the source of legal material is obtained from primary legal materials, namely the applicable legislation and secondary legal material obtained from literature or scientific work that is relevant to the problem appointed. Legal material collection techniques with document studies and legal material analysis are processed systematically and the results are presented in descriptive analysis. From the results of this study it can be concluded that the procedure for unilaterally terminating contracts in the procurement of goods / services contracts is preceded by giving warnings (summons), proving meetings (Show Cause Meeting) and giving Test Cases and legal consequences of unilateral termination of contracts. Contract for the procurement of goods / services is the imposition of administrative sanctions, blacklisted sanctions, civil claims and criminal reporting to the authorities.